Siberia in the work of Pierre Leroy-Beaulier “Renewal of Asia: Siberia, China, Japan” - E. M. Moiseeva; S. A. Kovalevsky (Гуманитарные и юридические исследования)
Introduction. The article discusses the representation of Siberia in the work of the French author Pierre LeroyBeaulieu “The Renewal of Asia: Siberia, China, Japan” (1900).Materials and Methods. “The Renewal of Asia: Siberia, China, Japan” has not been translated into Russian and is being introduced into scientific circulation for the first time. It presents a positive image of Russia. Pierre Leroy-Beaulieu's paper is a serious work based on statistics, scientific research and personal observations that he made during his trips in Siberia. The work uses the methodological principles of the interdisciplinary scientific direction of imagology, as well as research approaches of spatial imperial history, which involves not only the study of the practices of space development, but also its representation.Analysis. With the reference to specific examples the article examines how Pierre Leroy-Beaulieu constructed the space of the “new” Siberia. He associated the renewal of Siberia with the construction of the Trans-Siberian Railway, which he considered “the masterpiece of the century”. The author focused the reader’s attention on evidence of progress and urbanization, wrote about the potential of Siberia, but did not forget about the problems and obstacles to development. He destroyed the markers of mystery and danger of this territory and the image of Siberia with ”bad reputation” that existed in French discourse. The article examines how the author helped his readers to “imagine” the great spaces of Siberia. Comparing the space of Siberia with the space of North America, the author sought to make Siberia understandable to Europeans and mentally bring the space of Siberia closer. The image of Siberian cities in the work of Pierre Leroy-Beaulieu is studied. Attention is paid to the author's idea of the tolerance of Russians and their relationships with the native population. The article will also present facts from the biography of the author, who came from the well-known Leroy-Beaulieu family.Results. The analysis of the source showed that in place of the old image of Siberia with a «bad» reputation, which did not correspond to the new realities of the late 19th – early 20th centuries, the image of a “new” Siberia was constructed in French discourse.